SJMHE1 Peptide from Schistosoma japonicum Inhibits Asthma in Mice by Regulating Th17/Treg Cell Balance via miR-155 - Li L; Shan W; Zhu H; Xue F; Ma Y; Dong L; Feng D; Mao J; Yuan G; Wang X (Dove Medical Press, 2021)
Li Li,1,2,* Wenqi Shan,1,3,* Haijin Zhu,1,3,* Fei Xue,1,2 Yongbin Ma,1,4 Liyang Dong,1,5 Dingqi Feng,1 Jiahui Mao,1 Guoyue Yuan,6 Xuefeng Wang1,5 1Department of Central Laboratory, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People's Republic of China; 2Department of Clinical Laboratory, The Taixing City People's Hospital, Taixing, 225400, People's Republic of China; 3Department of Pediatrics, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People's Republic of China; 4Department of Central Laboratory, Jintan Hospital, Jiangsu University, Jintan, 213200, People's Republic of China; 5Department of Nuclear Medicine and Institute of Oncology, The Affiliated Hospital of Jiangsu University, Zhenjiang, 212001, People's Republic of China; 6Department of Endocrinology, The Affiliated Hospital of Jiangsu University, Zhenjiang, Jiangsu, 212001, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Wang; Liyang DongDepartment of Central Laboratory, The Affiliated Hospital of Jiangsu University, 438 Jiefang Road, Zhenjiang, 212001, People's Republic of ChinaTel +86-511-8502-1135; +86-511-8502-6569Email xuefengwang@ujs.edu.cn; dongliyang0829@hotmail.comPurpose: Helminths and their products can regulate immune response and offer new strategies to control and alleviate inflammation, including asthma. We previously found that a peptide named as SJMHE1 from Schistosoma japonicum can suppress asthma in mice. This study mainly investigated the molecular mechanism of SJMHE1 in inhibiting asthma inflammation.Methods: SJMHE1 was administered to mice with OVA-induced asthma via subcutaneous injection, and its effects were detected by testing the airway inflammation of mice. The Th cell distribution was analyzed by flow cytometry. Th-related transcription factor and cytokine expression in the lungs of mice were analyzed using quantitative real-time PCR (qRT-PCR). The expression of miR-155 and levels of phosphorylated STAT3 and STAT5 were also determined after SJMHE1 treatment in mice by qRT-PCR and Western blot analysis. The in vitro mouse CD4+ T cells were transfected with lentivirus containing overexpressed or inhibited miR-155, and the proportion of Th17, Treg cells, CD4+p-STAT3+, and CD4+p-STAT5+ cells were analyzed by flow cytometry.Results: SJMHE1 ameliorated the airway inflammation of asthmatic mice, upregulated the proportion of Th1 and Treg cells, and the expression of Th1 and Treg-related transcription factor and cytokines. Simultaneously, SJMHE1 treatment reduced the percentage of Th2 and Th17 cells and the expression of Th2 and Th17-related transcription factor and cytokines. SJMHE1 treatment decreased the expression of miR-155 and p-STAT3 but increased p-STAT5 expression. In vitro, the percentage of Th17 and CD4+p-STAT3+ cells increased in CD4+ T cells transfected over-expression of miR-155, but SJMHE1 inhibited the miR-155-mediated increase of Th17 cells. Furthermore, SJMHE1 increased the proportion of Treg and CD4+p-STAT5+ cells after transfected over-expression or inhibition of miR-155.Conclusion: SJMHE1 regulated the balance of Th17 and Treg cells by modulating the activation of STAT3 and STAT5 via miR-155 in asthma. SJMHE1 might be a promising treatment for asthma.Keywords: Schistosoma japonicum peptide, SJMHE1, Th17/Treg cell balance, miR-155, asthma